Efeito do estádio de maturidade sobre o valor nutritivo da silagem de sorgo forrageiro - Sorghum bicolor (L) moench, cultivar EA-116. - Barrocas, Fernando Airton Lopes (1983)
This work was carried out at the facilities of the Departamento de Zootecnia da Universidade Federal do Ceará, Brasil with the objetive of studying the effect of the stage of maturity on the nutritive value of the silage of sorghum, cultivar EA-116, through digestibility trials sheep. The experimental treatments were: A - silage of sorghum cut at milky stage, 70 days after planting; B - silage of sorghum cut at soft dough grain stage, 80 days after planting; C - silage of sorghum cut at hard dough grain stage, 90 days after planting; D - silage of sorghum cut at hard grain stage, 100 days after planting. The experiment folwed a complete randomized design with four treatments and three replications, constituted by one animal each. Adult,castrated, caudetomized males were used, kept in metabolic cages. The sorghum forage dry matter percentages were 26.7; 29,9; 31.4, and 34.7, respectivily for treatments A, B, C and D. On the otherhand, the silages presented 24.15; 26.64; 31,57 and 34,39 dry matter, 6.98; 7.36; 7.44 an 7.00% crude protein and 3.03; 3.14; 3.25 and 3.13 kcal/g total energy, respectively for treatments A, B, C and D. The apparent digestibility coeficients for the same order of treatments were 45.5; 46.9; 45.8 and 51,9% for the dry matter, 42,4; 40.4; 45.2 and 45.2 for protein and 31.8; 34,3; 36.9 and 41.4 for total energy. The dry matter intake was 1.68; 1.79; 1.82 and 2.08 kg of dry matter/100kg of live weight, whereas the digestible dry matter intake was 19.1; 21.1; 20.7 and 27.7 kg0,75, respectively for treatments A, B, C and D. The crud protein ingestions for treatments A, B, C e D were 2.8; 3.3; 3.4 and 3.7 g/kg0,75 .33; 1.53 and the digestible protein intake was 1.19; 1.33; 1.53 and 1.68 g/kg0,75, for the same order of treatments. The total and the digestible energy ingestions were 124.9 and 37.7 kcal/kg0,75, for treatments A, 141.7 and 48.8 kcal/kg0,75 for treatment B 149.1 and 55.0 kcal/kg0,75 for treatment C and 167.5 and 69.5 kcal/kg0,75, for treatment D. Nitrogem retention in treatments A, B, C and D was respectively 0,25; 0,97; 1.00 and 2.00 g/animal/day the percentages of retained over the ingested nitrogem were 4.23; 12.10; 12.84 and 20.30% for the same order of treatments. It was concluded that, on the conditions under which the research was carried out, the silage of shorghum, cultivar EA-116, cut at 100 days of age resulted on the higlest nutritive value and ingestion by sheep.